Biomarkers of aging for the identification and evaluation of longevity interventions - Moqri, Mahdi; Herzog, Chiara; Poganik, Jesse R; Justice, Jamie; Belsky, Daniel W; Higgins-Chen, Albert; Moskalev, Alexey; Fuellen, Georg; Cohen, Alan A; Bautmans, Ivan; Widschwendter, Martin; Ding, Jingzhong; et al. (Cell, 2023)
With the rapid expansion of aging biology research, the identification and evaluation of longevity interventions in humans have become key goals of this field. Biomarkers of aging are critically important tools in achieving these objectives over realistic time frames. However, the current lack of standards and consensus on the properties of a reliable aging biomarker hinders their further development and validation for clinical applications. Here, we advance a framework for the terminology and characterization of biomarkers of aging, including classification and potential clinical use cases. We discuss validation steps and highlight ongoing challenges as potential areas in need of future research. This framework sets the stage for the development of valid biomarkers of aging and their ultimate utilization in clinical trials and practice.